PENGARUH BI RATE, INFLASI DAN KURS TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Catur Kumala Dewi, Shelna Shabrina, Titin Ruliana (EKONOMIA, 2018)
Shelna Shabrina: The Influence of BI Rate, Inflation and Exchange Rate on Banking Companies BUMNs listed on Indonesia Stock Exchange Period 2012-2016. (under the guidance of Supervisor I, Dr. Titin Ruliana and Supervisor II Catur Kumala Dewi).Banking has a strategic role in supporting the wheels of the economy and development and play an important role in controlling the stability and the economy in Indonesia. Bank Indonesia (BI) usually announces the benchmark rate (BI Rate) within a few days after the official release of the inflation rate. Because inflation is usually made as one of the factors to determine the BI Rate. The increase in the BI Rate is expected to further strengthen the control of inflation expectations and reduce the risk of possible effects of rupiah depreciation on inflation and vice versa.The purpose of this research is to test, know and explain the effect of BI Rate, Inflation and Exchange Rate to Stock Price. The independent variables used in this study are BI Rate, Inflation and Exchange Rate, while for the dependent variable in this research is Stock Price. The population in this research is BUMN Banking companies listed in Indonesia Stock Exchange period 2012-2016.This research uses classic assumption test consist of multicolinearity test, autocorrelation test, heteroscedasticity test, normality test, and using partial test (t test), simultaneous test (f test) and Analytical tool used is multiple regression analysis.Â The results of this study indicate that the variables BI Rate, Inflation and Exchange rate simultaneously have a significant positive effect on stock prices with Fcount of 4.672> Ftable of 2.642 with a significant level of 0.003 < a value of 0.05, while the results of this study show partially that variable BI Rate has negative and significant influence to share price with tcount of 2,172 > ttabel 1,970 with significant level of 0.031 < 0.05, Inflation variable has positive and insignificant effect on the price of sahan with tcount value of 1.106 < ttabel 1.970 with significant level of 0.270 > 0.05 , and exchange rate variable have positive and significant influence to share price with tcount of 3,656> ttabel 1,970 with significant level 0.000 < 0.05.The conclusion of this study shows that the BI Rate has a negative and significant effect partially on Stock Price, Inflation has positive and not significant partially to Share Price, Exchange rate has positive and partially significant to Share Price, BI Rate, Inflation and Exchange rate significantly simultaneous to Stock Price.